Financial Inclusion for Sustainable Development in Industry 4.0: A Bibliometric Study (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Financial inclusion has become a key driver in promoting sustainable development, especially in the era of Industry 4.0, which is characterized by rapid digitalization, technological innovation, and the transformation of financial services. Although academic interest in this topic continues to grow, research in this field has not been systematically mapped, resulting in limited understanding of global trends and thematic evolution. This study uses bibliometric analysis (BA) to explore developments, intellectual structures, and key research focuses in financial inclusion research. Data were collected from the Scopus database for the period 2015–2025, using keywords related to financial inclusion, thus ensuring a comprehensive dataset for analysis. Bibliometric methods were applied using analytical tools such as VOSviewer and R Studio to support the assessment. The results of the analysis show a consistent increase in the number of publications over the last decade, reflecting growing academic attention. The main contributions came from India, China, and the United States, with increasing participation from universities in Africa and Southeast Asia through international collaboration. The main research focus has shifted from microfinance and poverty alleviation to more digital-oriented themes, including fintech, digital finance, blockchain, and green finance. This study contributes by mapping the structure and trends of financial inclusion research and providing insights for policymakers and academics in developing inclusive financial systems that support national strategies such as the SNKI, MSME digitalization, and financial literacy programs in Indonesia to achieve sustainable development goals.